2008
DOI: 10.1111/j.1471-4159.2008.05677.x
|View full text |Cite
|
Sign up to set email alerts
|

The marine phycotoxin gymnodimine targets muscular and neuronal nicotinic acetylcholine receptor subtypes with high affinity

Abstract: Gymnodimines (GYMs) are phycotoxins exhibiting unusual structural features including a spirocyclic imine ring system and a trisubstituted tetrahydrofuran embedded within a 16‐membered macrocycle. The toxic potential and the mechanism of action of GYM‐A, highly purified from contaminated clams, have been assessed. GYM‐A in isolated mouse phrenic hemidiaphragm preparations produced a concentration‐ and time‐dependent block of twitch responses evoked by nerve stimulation, without affecting directly elicited muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
152
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(163 citation statements)
references
References 53 publications
10
152
0
1
Order By: Relevance
“…2 C and D and Table 2). Antagonism by GYM is consistent with data obtained on Xenopus myocytes and frog and mouse neuromuscular preparations (15). GYM also antagonizes ACh in oocytes expressing α4β2.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…2 C and D and Table 2). Antagonism by GYM is consistent with data obtained on Xenopus myocytes and frog and mouse neuromuscular preparations (15). GYM also antagonizes ACh in oocytes expressing α4β2.…”
Section: Resultssupporting
confidence: 79%
“…Later reports revealed that 13-desmethyl spirolide C caused dose-dependent, widespread mouse brain neuronal damage and up-regulation of muscarinic and nicotinic ACh receptors (nAChR) transcription in rats (2). In contrast to most peptidic toxins, gymnodimines target both muscle and neuronal nAChRs at subnanomolar concentrations, explaining their neurotoxicity (15).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to other cyclic imines, such as the structurally related pinnatoxins (Araoz et al, 2011) and spirolides (Gueret and Brimble, 2010), knowledge on gymnodimines is still limited. Gymnodimine A is a fast-acting toxin with high intraperitoneal toxicity in mice (LD 50 of 80e96 mg/kg) (Kharrat et al, 2008;Munday et al, 2004) and similar bioactivities have been reported from other cyclic imines (Munday, 2008). Gymnodimine A is of low oral toxicity to mice, and is regarded as low risk for humans (Munday et al, 2004).…”
Section: Introductionmentioning
confidence: 99%